Virtual-reality exergaming improves performance during high-intensity interval training. Issue 6 (3rd July 2019) - Farrow, Matthew; Lutteroth, Christof; Rouse, Peter C.; Bilzon, James L. J.
Abstract: Purpose: To determine if: (i) mean power output and enjoyment of high-intensity interval training (HIIT) are enhanced by virtual-reality (VR)-exergaming ( track mode) compared to standard ergometry ( blank mode), (ii) if mean power output of HIIT can be increased by allowing participants to race against their own performance ( ghost mode) or by increasing the resistance ( hard mode), without compromising exercise enjoyment. Methods: Sixteen participants (8 males, 8 females, VO2 max: 41.2 ± 10.8 ml −1 ·kg −1 ·min −1 ) completed four VR-HIIT conditions in a partially-randomised cross-over study; (1a) blank, (1b) track, (2a) ghost, and (2b) hard . VR-HIIT sessions consisted of eight 60 s high-intensity intervals at a resistance equivalent to 70% (77% for hard) maximum power output (PMAX ), interspersed by 60 s recovery intervals at 12.5% PMAX, at a self-selected cadence. Expired gases were collected and VO2 measured continuously. Post-exercise questionnaires were administered to identify differences in indices related to intrinsic motivation, subjective vitality, and future exercise intentions. Results: Enjoyment was higher for track vs. blank (difference: 0.9; 95% CI: 0.6, 1.3) with no other differences between conditions. There was no difference in mean power output for track vs. blank, however it was higher for track vs. ghost (difference: 5 Watts; CI: 3, 7), and hard vs. ghost (difference: 19 Watts; 95% CI: 15, 23). Conclusions: These findings demonstrate that VR-exergaming is an effective intervention to increase enjoyment during a single bout of HIIT in untrained individuals. The presence of a ghost may be an effective method to increase exercise intensity of VR-HIIT.